The death of scientific evidence in Canadian policymaking: Controversy and collective resistance to perceived government 'anti-science'. Issue 1 (5th March 2018) - Smart, Graham
Abstract : This study examines publicly voiced resistance by a Canada-wide community of scientists and citizen supporters against what they perceived as the Canadian government's efforts to undermine publicly supported science, with its concern for empirical evidence, in order to facilitate a narrowly pro-industry orientation in its policy-making. Using Hajer's argumentative discourse analysis (ADA) to interpret a corpus of some 700 Web-published texts, the author identified a macro-argument collectively produced and publicly communicated by the Canadian scientific community. The study also showed how this macro-argument served as a vehicle for two ideological representations: a virtuous self-representation of the scientific community itself and a negative representation of the motives and actions of the Canadian government. The findings of the research contribute to our understanding of how collective argumentative positions emerge within the discourse of a major scientific controversy. At the same time, the study offers policymakers insights in how they might communicate more effectively with communities of scientific experts.